2018
DOI: 10.1007/s13201-018-0742-6
|View full text |Cite
|
Sign up to set email alerts
|

Short-term prediction of groundwater level using improved random forest regression with a combination of random features

Abstract: To solve the problem where by the available on-site input data are too scarce to predict the level of groundwater, this paper proposes an algorithm to make this prediction called the canonical correlation forest algorithm with a combination of random features. To assess the effectiveness of the proposed algorithm, groundwater levels and meteorological data for the Daguhe River groundwater source field, in Qingdao, China, were used. First, the results of a comparison among three regressors showed that the propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…In the last few years, other ensemble and conventional ML models are also developed to predict GWL prediction for sustainable water resource management [39], [40]. In [39] the authors presented an ensemble model based on KNN and RF for three months ahead of groundwater table prediction based on seasonal changes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, other ensemble and conventional ML models are also developed to predict GWL prediction for sustainable water resource management [39], [40]. In [39] the authors presented an ensemble model based on KNN and RF for three months ahead of groundwater table prediction based on seasonal changes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In [39] the authors presented an ensemble model based on KNN and RF for three months ahead of groundwater table prediction based on seasonal changes. In [40], the authors proposed an enhanced RF prediction model based on the combination of random features to forecast GWL using two features; temperature (Celsius) and precipitation (Millimeters). The authors reported that the R2 score value of the enhanced RF is 0.8223 for long-term forecasting, which is still improvable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ganga Devi [21] applied Random Forests model for predicting the groundwater quality class label and to check the groundwater from the study area is suitable for drinking purpose or not. Wang et al [22] proposed an enhanced random forest model for short term prediction groundwater level of Daguhe River groundwater source field, in Qingdao, China.…”
Section: Literature Surveymentioning
confidence: 99%
“…The results demonstrated that the RF model has superior predictive capabilities with fewer parameters and training time. Decision tree-based models have been successfully applied in groundwater hydrological modeling (Singh et al, 2014;Wang et al, 2018). Marques et al (2005) used ML algorithms to optimize water supply for crops at different growing stages, given the water cost, the market price, cost of irrigation, crop expenses, and expected yield reduction due to under-or overirrigation throuhout the entire growing period.…”
Section: Introductionmentioning
confidence: 99%